Investigation of Neologism in Promotional Text on Instagram - Mulyati Khorina; Zaqi Herdiansyah; Mohammad Febryanto (Jurnal Bahasa Inggris Terapan, 2021)
The development of information technology has impacted any aspect of life including marketing products and services. One platform which has become popular is Instagram. Recently, advertisements tend to use new words to promote their goods or services. There are many ways to make a new word which is commonly called a neologism. One of them is a blend. Blend means combining two or more words using clipping, overlapping, or both clipping and overlapping. Therefore, this study is aimed at investigating the frequent blended words found in online advertisements, especially on social media and websites. The present project used the qualitative method since the data of this study was in the form of text which is a characteristic of qualitative methods. The data were taken from promotional texts in the “Giladiskonn” account on Instagram in 2021. Using the morphosemantics approach, the results of the analysis showed that portmanteau words were created using various types of clipping. The clipping process may occur on the first, second, or both words. The findings can be used to improve learners’ vocabulary and the model to create new words in promotional texts.